Oncolytic virus OH2 extends survival in patients with PD-1 pretreated melanoma: phase Ia/Ib trial results and biomarker insights - Juan Li; Xuan Wang; Li Zhou; Jun Guo; Lu Si; Bixia Tang; Chuanliang Cui; Xiaoting Wei; Xinan Sheng; Siming Li; Zhihong Chi; Lili Mao; et al. (Journal for ImmunoTherapy of Cancer)
Background OH2 is an oncolytic virus derived from herpes simplex virus type 2. A phase Ia/Ib clinical trial in China was conducted in patients with unresected stage III–IV melanoma, the majority of whom had the acral type, to assess the safety and preliminary efficacy of OH2.Methods The trial enrolled patients with histologically confirmed unresectable stage III or advanced stage IV melanoma. In phase Ia, nine patients received OH2 single-dose treatment across three dose levels (106, 107, and 108 CCID50/mL, where CCID50 represents cell culture infectious dose 50%) while six patients underwent multidose therapy. Phase Ib expanded the proposed dose. Antitumor efficacy was evaluated using the Response Evaluation Criteria in Solid Tumors and immune-RECIST guidelines. NCT04386967 is the clinical trial identifier.Results All 44 patients were enrolled. OH2 was well tolerated without serious adverse events (AEs) or deaths reported. No Grade 3 or higher treatment-related AEs occurred. In phase Ia, the 1-year survival rate was 92.9% (95% CI, 59.1% to 99.0%), with a median overall survival of 28.9 months (95% CI, 12.7 to not reached). In phase Ib, 10 patients achieved immune-partial response (iPR)/partial response (PR), yielding an objective response rate (ORR) of 37.0% (95% CI, 19.4% to 57.6%), with 6 patients still responding. The rate of the durable response (PR or complete response lasting at least 6 months) was at least 29.6% (8/27). Notably, 7 of 12 III–IVM1a patients who previously received programmed cell death protein-1 (PD-1) therapy achieved iPR/PR, with an ORR of 58.3% (95% CI, 27.7% to 84.8%) and a disease control rate of 75.0% (95% CI, 42.8% to 94.5%). Biomarker analysis indicated that elevated baseline neutrophil activation state correlated with poorer clinical outcomes. A phase III clinical trial is ongoing in China (NCT05868707).Conclusions OH2 oncolytic virotherapy exhibited a favorable safety profile without dose-limiting toxicities (DLTs) and demonstrated durable antitumor efficacy in patients with melanoma, especially in those who had progressed on anti-PD-1 treatment.Trial registration number ClinicalTrials.gov identifier NCT04386967.